The Fimbrial Gene z3276 in Enterohemorrhagic Escherichia coli O157:H7 Contributes to Bacterial Pathogenicity - Zhang, Bicheng; Sun, Xiaohan; Fan, Hongjie; He, Kongwang; Zhang, Xuehan (Frontiers in Microbiology, 2018)
Enterohaemorrhagic Escherichia coli (EHEC) O157:H7 is a zoonotic pathogen of worldwide importance that causes foodborne infections in humans. It is not capable of expressing type I fimbrial because of base deletion in the fim operon. BLAST analysis shows that the open reading frame z3276, a specific genetic marker of EHEC O157:H7, encodes a sequence with high amino acid identity to other E. coli type I fimbrial, but its definitive function in EHEC O157:H7 remains unclear. We are here to report that a z3276 mutant (△z3276) was constructed using the reference EHEC O157:H7, the mutant △z3276 was biologically characterized, and the pathogenicity of △z3276 was assessed in mice in comparison with the wild type (WT) strain. Motility and biofilm formation assays revealed a smaller twitching motility zone for △z3276 on the agar surface and significantly decreased biofilm formation by △z3276 compared with the parental strain. The adhesion and invasion ability of △z3276 to HEp-2 cells showed no significant change, but the invasion ability of △z3276 to IPEC-J2 cells was attenuated. Furthermore, in the animal study, we observed shortened and lower fecal shedding among the △z3276 mutant-infected animals compared with those infected WT strain. The data in this study indicate that this unique gene of z3276 in EHEC O157:H7 seems to play an important role in bacterial pathogenicity.